Effects of tax exemption on economic growth - Marconi Silva Miranda; Marco Aurélio Marques Ferreira; Luiz Antônio Abrantes; Suélem Viana Macedo (BBR: Brazilian Business Review)
Faced with economic crisis and stagnation, the Brazilian government, in the fiscal realm, has been characterized by the adoption of exemption tax policies. In this scenario, the present study aimed to investigate the behavior of some dimensions of industrial activity, having as its central focus the effect that the Tax on Industrialized Products exemptions has on the economic growth of Brazilian municipalities. The empirical strategy employed used statistical models in panel data and quantile regression, taking the period between 2007 and 2017. The main results indicated that, even with the positive behavior of industrial activity, especially between 2009 and 2013, the exemptions did not contribute to the economic growth of Brazilian municipalities.